STUDI PENERAPAN ASUHAN KEBIDANAN PADA BAYI BARU LAHIR Ny F DENGAN MASALAH IKTERUS FISIOLOGIS - Mila Sari Agustina; Nur Hidayati; Inna Sholicha Fitriani (Universitas Muhammadiyah Ponorogo, 2022)
Newborns are babies who are born normal, full term, and weigh 2,500-4000 grams, cry loudly, and without congenital abnormalities. With the provision of midwifery care for newborns, it can help reduce IMR and provide welfare for BBL. This care uses the midwifery management approach and the SOAP method. By using a descriptive qualitative research method through a case study approach using midwifery management steps such as conducting assessments, determining diagnoses, planning care, conducting interventions, making evaluations, and documenting midwifery care. Midwifery care in pregnancy given to Mrs. F 39-40 weeks gestation. The baby was born spontaneously with the help of a midwife, weight 3,400 grams, PB 50cm, LK 33cm, LD 32cm, male gender. BBL visits were carried out 2 times starting from February 16, 2021 to February 21, 2021 and when the second visit was found a problem in the baby, namely physiological jaundice, the midwife gave advice to the mother to breastfeed the baby constantly at least every 2 hours and dry the baby in the morning around 07.00 -09.00 WIB within 15 minutes. Continuity of midwifery care given to Mrs. F has been carried out, the problems experienced by the baby can be resolved properly so that the baby's condition is in good health. It is hoped that midwives can maintain quality and quality services based on midwifery service standards. So that it can prevent the occurrence of neonatal emergencies, in order to reduce the infant mortality rate.